Implementasi Praktik Shopee Paylater Dalam Perspektif Ba’i As-Salam - Musanna, Khadijatul (Universitas Islam Negeri Sumatera Utara, 2024)
Shopee Paylater is a payment method in installments, buy goods with a pre-order system and pay later. Shopee Paylater is almost the same as a buying and selling system that uses a Ba'i As-salam contract. This research is classified as qualitative with a normative juridical research approach. The purpose of the study was to determine the legal status contained in Shopee Paylater regarding whether it was in accordance with the Ba'i As-salam contract. The research method used is qualitative with a normative juridical approach, Shopee Paylater is analyzed based on the Ba'i As-salam theory. As for the results of the research, it is true that Shopee Paylater has complied with the provisions of the Shari'a as contained in the Ba'i As-salam, but due to additional costs when paying installments on the loan, this changes the legal status of Shopee Paylater into a prohibited transaction because the additional referred to contain usury. As stated in the Qur'an, Allah has permitted buying and selling and forbade usury.Keywords: Implementation, Shopee Paylater, Ba'i As-Salam